PRINCIPLES OF OPERATIONAL COMMUNICATIONS SYSTEM - Colonel (ret.) Professor Gruia TIMOFTE, Ph.D (Annals: Series on Military Sciences)
This article includes a brief analysis of the principles of tactical and operational communication systems used in modern combat space, highlighting their requirements and qualities in ensuring an optimal information flow for the development of complex military actions. They are the core around which they develop and satisfy the requirements for command and control, as well as for complex integrated systems (C3I, C4I, C4ISR, C4IRISTA. etc.) being substantiated and developed in the following period. The continuously growing information requirements and the explosive technological developments in the field require the highest priority approach to the study, design and realization in record time of the means for these integrated systems.